Inheritance : a memoir of genealogy, paternity, and love - Shapiro, Dani (New York : Alfred A. Knopf, 2019)
"In the spring of 2016, through a genealogy website to which she had whimsically submitted her DNA, Dani Shapiro received the astonishing news that her beloved deceased father was not her biological father. Over the course of a single day, her entire history--the life she had lived--crumbled beneath her. In just a few hours of Internet sleuthing, she was able to piece together the story of her conception and, remarkably find a YouTube video of her biological father--his face and mannerisms eerily similar to her own. [This] is a book about secrets--secrets within families, kept out of shame or self-protectiveness; secrets we keep from one another in the name of love. It is the story of a woman's urgent quest to unlock the story of her own identity, a story that had been scrupulously hidden from her for more than fifty years. It is a book about the extraordinary moment we live in, a moment in which science and technology have outpaced not only medical ethics but also the capacities of the human heart to contend with the consequences of what we discover. Dani Shapiro's memoir unfolds at a breakneck pace--part mystery, part real-time investigation, part rumination on the ineffable combination of memory, history, biology, and experience that makes us who we are"--
Keywords: Shapiro, Dani; Women novelists, American -- Biography; Novelists, American -- 20th century -- Biography; Jewish women -- United States -- Biography; Fathers and daughters -- United States -- Biography; Autobiographies